Processing Critical Bond Lenght Berdasarkan Data Aktual Pull Out Test (Cablebolt) pada Area Tambang Bawah Tanah Grasberg Block Cave Di PT.Freeport Indonesia - Mofu, Raynata Aprillia; Wijaya, R.Andy Erwin; Sutrisno, Agung Dwi (Jurnal of Mining Insight, 2023)
PT. Freeport Indonesia is a company that mines, processes and explores ores containing copper, gold and silver in the highlands of Tembagapura, Mimika Regency, Papua Province with an area of 212,950 hectares. To improve the stability of the opening hole in underground mines, it is necessary to implement  a ground support  system in underground mines, one of which is used in  the Grasberg Block Cave (GBC) area of PT. Freeport Indonesia is a supporting support (Cable bolt). Therefore, it is necessary to further analyze the strength of the critical bond length  of the Cablebolt in the Grasberg Block Cave (GBC) area of the underground mine of PT. Freeport Indonesia. The purpose of this study is (1) to determine the strength of the bond length based on tensile test data, (2) to determine the elastic value of cable bolts. From the results of the tension and strain of the single cable bolt that has been obtained, the Ice Value and the maximum stress of the cable bolt are determined, the data is obtained with a tension value of 10.6263 N/mm2 and a stretch value of 0.00427. After obtaining the stress and tension values of the single cable bolt,  the Es value of the cable bolt with a value of 1403.45 Mpa is sought. From the results of the tension and tension of the twin  cable bolts that have been obtained, the Ice value of the cable bolts is obtained. From the experimental data, a tensile value of 3.8658 N/mm2 and a tensile value of 249.68 were obtained. After obtaining the stress and tension values of the twin cable bolts, the Ice value of the cable bolts with a value of 358.647 Mpa is sought.